MODEL OF RULE PARAMETER CREATION FOR WAFER SCRAP PREVENTION IN THE APPLIED MATERIALS CENTURA 5200 METAL ETCHER PROCESS - Deraman, M.Z.; Ebrahim, Z.; Omar, G.; Hassan, W.F.; Chik, A.; Darmawan, Z. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Products with Integrated Circuits (IC) becomes necessity in daily life such as mobile phones, computers, televisions etc. In this regard, Etching stands out as the predominant procedure in the field of semiconductor manufacturing. This process involves a number of parameters and steps that requires close monitoring in order to be efficient and competitive by minimising the premature equipment failures. This study focuses on minimisation the number of wafers at risk during wafer fabrication at metal etch process. Design of Experiment approach was applied in identifying the key parameters with a significant relationship with equipment failures and root causes of wafer scraps. The key parameters were developed into smart decision matrix that integrates with SilTerra equipment monitoring systems. Then, the key parameters were optimised for Statistical Process Control (SPC) at the Metal Etching equipment named as Applied Material Centura 5200. This implementation enables the equipment to detect potential failures and stop the relevant process parameters. In this approach, the wafers can be secured from becoming scrap, resulting in a reduction in the cycle time required for additional testing. Accordingly, wafer scrap has been significantly reduced, resulting in a 56% decrease in the total wafer scraps from the equipment.